2018
DOI: 10.1002/ece3.4096
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of colonization of Oxalis alpina in the Sky Islands of the Sonoran desert via pollen and seed flow

Abstract: Historical factors such as climatic oscillations during the Pleistocene epoch have dramatically impacted species distributions. Studies of the patterns of genetic structure in angiosperm species using molecular markers with different modes of inheritance contribute to a better understanding of potential differences in colonization and patterns of gene flow via pollen and seeds. These markers may also provide insights into the evolution of reproductive systems in plants. Oxalis alpina is a tetraploid, herbaceou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
(114 reference statements)
2
1
0
Order By: Relevance
“…The small number of microsatellite loci used and their capability of detecting the true population structure is another plausible explanation for the discrepancy between this marker and mtDNA. Other recent studies using a similar number of microsatellite markers in other organisms ( Pérez-Alquicira et al, in press ; Villamor, Costantini & Abbiati, in press ; Zheng et al, in press ) also found significant genetic structure in some cases. Another study using the same microsatellite loci ( Maroja, Almeida & Seuánez, 2003 ) found significant genetic differentiation in N. squamipes samples from a very small geographic area (maximum distance among sites = 6 km).…”
Section: Discussionsupporting
confidence: 63%
“…The small number of microsatellite loci used and their capability of detecting the true population structure is another plausible explanation for the discrepancy between this marker and mtDNA. Other recent studies using a similar number of microsatellite markers in other organisms ( Pérez-Alquicira et al, in press ; Villamor, Costantini & Abbiati, in press ; Zheng et al, in press ) also found significant genetic structure in some cases. Another study using the same microsatellite loci ( Maroja, Almeida & Seuánez, 2003 ) found significant genetic differentiation in N. squamipes samples from a very small geographic area (maximum distance among sites = 6 km).…”
Section: Discussionsupporting
confidence: 63%
“…The small number of microsatellite loci used and their capability of detecting the true population structure is another plausible explanation for the discrepancy between this marker and mtDNA. Other recent studies using a similar number of microsatellite markers in other organisms (Pérez-Alquicira et al, 2018;Villamor et al, 2018;Zheng et al, 2018) also found significant genetic structure in some cases. Another study using the same microsatellite loci found significant genetic differentiation in N. squamipes samples from a very small geographic area (maximum distance among sites = 6 km).…”
Section: Discussionsupporting
confidence: 62%
“…But this is not always the case. With respect to the issue of clines, latitudinal variation has been detected within some SW and NoM species, which has been argued to have resulted from the movement of populations as glaciers advanced and retreated during the Pleistocene (e.g., Perez-Alquicira, Weller, Domínguez, Molina-Freaner, & Tsyusko, 2018;Potter, Hipkins, Mahalovich, & Means, 2015). In addition, a suture zone has been postulated to exist between southeastern Arizona and southwestern New Mexico in which hybrid zones between trees, birds, and mammals appear to be concentrated above background (Swenson & Howard, 2005).…”
Section: Generality To Other Systemsmentioning
confidence: 99%